Application of SEFTnobirthing-Ball To The Progress of Childbirth Process In Maternity Mother Primigravida In BPM Ika Siswiyanti Demak City - Anis Laela Megasari; Rizka Adela Fatsena (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Background: The maternal mortality rate in Indonesia is 38 thousand every day. One of the causes of the high mortality rate in Indonesia is prolonged labor. Prolonged labor is a labor process that lasts more than 24 hours in primiparas. There were 29 cases of old labor at the Independent Midwife Practice Ika Siswiyanti in Demak City in 2020, there were 29 cases, and all of these cases were referred. Self-birthing-ball is a combination of Spiritual Emotional Freedom Technique intervention with birthing ball that can reduce pain intensity and speed up the duration of labor. This study aims to determine the effect of self-birthing-ball on the progress of the first stage of labor in primigravida mothers. Methods: The design of this study was a Quasy experimental with a post-test only design. The research sample was 16 respondents obtained through purposive sampling, namely prospective respondents must meet the inclusion and exclusion criteria that have been determined. Statistical tests using Wilcoxon test. Results: The average percentage of labor progress is 3.2. statistical results obtained a p-value 0.031 (0.05), which shows that there has been an effect SEFTnobirthing-ball on the progress of the first stage of labor in primigravida mothers. Conclusion: SEFTnobirthing-ball proven to increase the progress of the first stage labor. Keywords: Birthing-ball; labor progress; first stage labor; SEFT